KOMUNIKASI PIMPINAN DALAM MENGATASI KONFLIK PEGAWAI - Dina Octavia; Jufri Halim (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2018)
ABSTRACK The purpose of this study is to find out how the leadership communication in addressing employee conflict in the planning and finance of regional office VI State Personnel Board Medan. Conflict is an aspect that can not be avoided and to overcome it required good communication. The research is qualitative research using interview and literature method. Communication indicators for effective understanding, pleasure, influence on attitudes, and better relationships. The results of the research that has been done is good enough and the conflicts that exist in the Planning and Finance Division of Regional Office VI Badan Kepegawaian Negara Medan is not much.  Keywords: Communication, Conflict and leadership